High Prevalence of Extended-Spectrum β-Lactamase Producing Enterobacteriaceae Among Clinical Isolates From Cats and Dogs Admitted to a Veterinary Hospital in Switzerland - Zogg, Anna Lena; Simmen, Sabrina; Zurfluh, Katrin; Stephan, Roger; Schmitt, Sarah N.; Nüesch-Inderbinen, Magdalena (Frontiers in Veterinary Science, 2018)
Objectives: This study aimed to identify and characterize extended-spectrum ß-lactamase (ESBL) producing Enterobacteriaceae among clinical samples of companion animals. Methods: A total of 346 non-duplicate Enterobacteriaceae isolates were collected between 2012 and 2016 from diseased cats (n=115) and dogs (n=231). The presence of blaESBL, PMQR genes and the azithromycin resistance gene mph(A) was confirmed by PCR and sequencing of bla genes. Isolates were further characterized by antimicrobial resistance profiling, multilocus sequence typing, phylogenetic grouping, identification of mutations in the QRDR of gyrA and parC and screening for virulence associated genes. Results: Among the 346 isolates, 72 (20.8%) were confirmed ESBL producers (58 E. coli, 11 Klebsiella pneumoniae, and three Enterobacter cloacae). The strains were cultured from urine (n=45), skin and skin wounds (n=8), abscesses (n=6), surgical sites (n=6), bile (n=4), and other sites (n=3). ESBL genes included blaCTX-M-1, 14, 15, 27, 55, and blaSHV-12, predominantly blaCTX-M-15 (54.8%, 40/73), and blaCTX-M-1 (24.7%, 18/73). Further genes included qnrB (4.2%, 3/72), qnrS (9.7%,7/72), aac(6’)-Ib-cr (47.2%, 34/72), and mph(A) (38.9%, 28/72). Seventeen (23.6%) isolates belonged to the major lineages of human pathogenic K. pneumoniae ST11, ST15, and ST147 and E. coli ST131. The most prevalent ST was E. coli ST410 belonging to phylogenetic group C. Conclusions: The high prevalence of ESBL producing clinical Enterobacteriaceae from cats and dogs in Switzerland and the presence of highly virulent human related K. pneumoniae and E. coli clones raises concern about transmission prevention as well as infection management and prevention in veterinary medicine.